Biostimulants induce positive changes in the radish morpho-physiology and yield - Raza, Qurat-Ul-Ain; Bashir, Muhammad Amjad; Rehim, Abdur; Ejaz, Rafia; Raza, Hafiz Muhammad Ali; Shahzad, Umbreen; Ahmed, Faraz; Geng, Yucong (Frontiers in Plant Science, 2022)
The increasing population has generated an open challenge for the agriculture sector to provide enough food in a sustainable environment. The upsurge in chemical fertilizers to enhance food production resulted in environmental problems. The objective of the current study was to utilize biostimulants for sustainable agricultural production as an alternative to chemical fertilization. For said purpose, two pot experiments were conducted to examine the response of radish against the sole and combined application of biostimulants. In the first experiment, effects of chemical fertilizer (CK), glycine (G), lysine (L), aspartic acid (A), and vitamin B complex (V) were studied. The results demonstrated that V has significantly improved the transpiration rate (81.79%), stomatal conductance (179.17%), fresh weight (478.31%), and moisture content (2.50%). In the second experiment, tested treatments were chemical fertilizer (CK), Isabion® (I), glycine + lysine + aspartic acid (GLA), moringa leaf extract + GLA (M1), 25% NPK + M1 (M2). The doses of biostimulants were 5g L-1 glycine, 1g L-1 lysine, 2g L-1 aspartic acid, and 10 ml L-1 moringa leaf extract. The photosynthetic rate was improved significantly with GLA (327.01%), M1 (219.60%), and M2 (22.16%), while, the transpiration rate was enhanced with GLA (53.14%) and M2 (17.86%) compared to the Ck. In addition, M1 increased the stomatal conductance (54.84%), internal CO2 concentration (0.83%), plant fresh weight (201.81%), and dry weight (101.46%) as compared to CK. The study concludes that biostimulants can effectively contribute to the sustainable cultivation of radish with better growth and yield.